Pengaruh Kesadaran Wajib Pajak, Sanksi, Kualitas Pelayanan dan Sosialisasi pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Widiastini, Ni Putu Atik; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p03, 2020)
Motor vehicle tax is a tax on the ownership and / or control of motor vehicles. The purpose of this study is to obtain empirical evidence of the influence of taxpayer awareness, tax sanctions, service quality and tax information dissemination on tax compliance in paying motor vehicle tax in Denpasar. This research is located in the Joint Office SAMSAT Denpasar City. The number of samples used was 100 motor vehicle taxpayers which were calculated using the Slovin formula with the sample determination method used was accidental sampling. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that taxpayer awareness, tax sanctions, service quality and tax socialization have a positive effect on taxpayer compliance in paying motor vehicle tax at the Joint Office of SAMSAT Denpasar. Keywords: Taxpayer Awareness; Penalty; Service quality; Socialization; Obedience.